Kontekstualisasi Projek Penguatan Profil Pelajar Pancasila (P5) dalam Kurikulum Merdeka di SD Negeri 44 Bengkulu Selatan - Pratiwi, Sindy Nur Fidia; Parmadi, Bambang; Kurniawati, Ike (Universitas Bengkulu, 2026)
This study aims to describe the contextualization of the Pancasila Student Profile Strengthening Project (P5) within the implementation of the Merdeka Curriculum at SD Negeri 44 Bengkulu Selatan. The Merdeka Curriculum emphasizes character development aligned with Pancasila values through project-based learning. Contextualization is crucial to connect P5 with local culture and community potential, ensuring meaningful learning experiences for students. The research employed a qualitative descriptive approach with data collected through interviews, observations, and documentation involving teachers, the principal, and students. Data analysis was conducted through data reduction, display, and verification, with triangulation for validity. The findings reveal that the contextualization process of P5 at SDN 44 Bengkulu Selatan is carried out through stages of planning, implementation, and evaluation. Planning involved theme selection and integration of local culture and entrepreneurship. Implementation emphasized collaboration, creativity, and student-centered learning activities. Evaluation was conducted through reflection and authentic assessment involving teachers and students. Despite several challenges such as limited resources and teachers’ understanding of contextualization strategies, the project contributed positively to the internalization of Pancasila values, preservation of local culture, and development of students’ creativity and independence. The study suggests the need for continuous teacher training and support facilities to strengthen contextualized P5 implementation.